Intervenção urbana e dança: um estudo das performances e relações de poder a partir das obras Aparecidas e Escape - Marques, José Jayme da Silva (2020)
This research is based on a performance study and it relations of power that exist in the artistic dance practice. How is it aesthetically organized and how it could be understood as urban Interventions. To exemplify this theory, we analyze two urban interventions from the city of Goiânia-GO, Brazil. “Aparecidas” was produced by ¿por quá? grupo que dança and “Escape” was produced by Nômades Grupo de Dança. Both interventions were developed and performed in between 2017 and 2018. This research verifies how the relations of power were developed by both groups in the artistic project previously mentioned. Analyzing both interventions from an observer point of view during the creative period. To work on it we will talk about arts: what is art, what is the artistic object, what is and who belong to the art world questioning their relation itself. We will contextualize cultural performance and performance art developing their historical link. That connection intends to bring us to what are urban interventions. In that way we can understand how are they dependent of social relations and interactions. By the end we will consider the human factor and its cultures, clarifying how it could be understood as power relations. We will use theories about power to identify in the artistic practice reflections about their compositions; describing both artistic experiences with the urban interventions analyzing the human relations from the beginning of the production to it exhibition.